2010
DOI: 10.1016/j.molcel.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

A DNAJB Chaperone Subfamily with HDAC-Dependent Activities Suppresses Toxic Protein Aggregation

Abstract: Misfolding and aggregation are associated with cytotoxicity in several protein folding diseases. A large network of molecular chaperones ensures protein quality control. Here, we show that within the Hsp70, Hsp110, and Hsp40 (DNAJ) chaperone families, members of a subclass of the DNAJB family (particularly DNAJB6b and DNAJB8) are superior suppressors of aggregation and toxicity of disease-associated polyglutamine proteins. The antiaggregation activity is largely independent of the N-terminal Hsp70-interacting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
504
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 333 publications
(582 citation statements)
references
References 45 publications
56
504
11
Order By: Relevance
“…Therefore, we tested which of the Drosophila small HSPs could suppress aggregation of an EGFP‐tagged huntingtin exon‐1 containing 119 glutamines (EGFP‐HDQ119) in S2 cells. The Dm ortholog of the human DNAJB6, MRJ, previously identified in a screen for suppressors of polyglutamine (polyQ) toxicity (Fayazi et al ., 2006; Hageman et al ., 2010) was used as a positive control and indeed completely inhibited aggregate formation in S2 cells as demonstrated using filter trap binding (Fig. 4A).…”
Section: Resultsmentioning
confidence: 74%
“…Therefore, we tested which of the Drosophila small HSPs could suppress aggregation of an EGFP‐tagged huntingtin exon‐1 containing 119 glutamines (EGFP‐HDQ119) in S2 cells. The Dm ortholog of the human DNAJB6, MRJ, previously identified in a screen for suppressors of polyglutamine (polyQ) toxicity (Fayazi et al ., 2006; Hageman et al ., 2010) was used as a positive control and indeed completely inhibited aggregate formation in S2 cells as demonstrated using filter trap binding (Fig. 4A).…”
Section: Resultsmentioning
confidence: 74%
“…All these studies have identified genes belonging to distinct classes including genes involved in RNA metabolism (RNA pol II subunits, splicing factors), protein synthesis (ribosomes, initiation and elongation factors), protein folding (chaperones) and protein degradation (proteasome subunits and autophagy factors). The role of molecular chaperones, particularly Hsp70 and Hsp40, in suppressing Htt aggregation and its associated toxicity has been extensively elucidated using different experimental approaches (Hageman et al, 2010;Muchowski et al, 2000;Sakahira et al, 2002;Warrick et al, 1999;Wyttenbach et al, 2000). Besides molecular chaperones, cells have evolved distinct mechanisms to protect themselves from accumulation of toxic protein species.…”
Section: Ii431 Huntington's Diseasementioning
confidence: 99%
“…However, among these different Hsp40 members, only DnaJB1 has been studied in detail. In HEK 293T cells, DnaJB1 is moderately expressed and is highly inducible upon heat stress (Hageman et al, 2010;Hageman et al, 2011). It has been shown that DnaJB1 suppresses the aggregation of polyQ proteins (Rujano et al, 2007;Zijlstra et al, 2010) and also prevents luciferase aggregation during heat stress (Hageman et al, 2010).…”
Section: Vi8 Role Of Dnajb1 In the Degradation Of Proteinsmentioning
confidence: 99%
See 2 more Smart Citations